Identifikasi Plankton pada Tambak Udang Vaname (Litopenaeus vannamei) di Teaching Factory Politeknik Kelautan dan Perikanan Pangandaran - Indra Kristiana; Wahyu Puji Astiyani; Atiek Pietoyo; Annisa Intan Maulidia; Muhammad Akbarurrasyid (Faculty of Science and Technology University Ibrahimy, 2024)
Vannamei shrimp (Litopenaeus vannamei) are one of the mainstays of Indonesia's aquaculture sector, which has great export potential. The development of Millennium Shrimp Farming (MSF) or millennial generation of shrimp farming means that the younger generation is encouraged to actively farm shrimp in a millennial way with the concept of cultivation using small amounts of land, low salinity and maximizing the regulation of water quality. Water quality in vannamei shrimp cultivation is managed by utilizing the application of probiotics and plankton growth. Plankton plays an important role in aquaculture, as natural food and an indicator of the fertility and stability of water bodies. Plankton itself is one of the main components in the food chain system and food web in vannamei shrimp cultivation. The aim of this research was to determine the type of plankton found in the vannamei shrimp ponds of Pangandaran Marine and Fisheries Polytechnic Teaching Factory. The data analysis method used is descriptive quantitative. The test parameters in this research were: plankton abundance, plankton diversity, plankton uniformity and dominance of plankton species found in vannamei shrimp ponds. The results of plankton identification in vannamei shrimp cultivation ponds in Pangandaran Maritime and Fisheries Polytechnic Teaching Factory revealed 7 species of plankton, including: (50-71)% from the Chlorophyta (green algae) group; (16-32)% from the Cyanophyta group (blue-green algae); (2-13)% from the Chrysophyta group (diatoms); 1% from the Phyrrophyta group (dinoflagellates); (2-3)% from the group of protozoa; (1-2)% from the Branchiopoda group and (2-8)% from the Euglenophyta group. The observation results show that the water in vannamei shrimp ponds has moderate biota community stability with plankton uniformity index values ​​under moderate or unstable conditions. Otherwise, there is no individual dominance in the shrimp pond waters.